The cytoplasmically-made subunit IV is necessary for assembly of cytochrome c oxidase in yeast. - Dowhan, W (1985)
Yeast cytochrome c oxidase contains three large subunits made in mitochondria and at least six smaller subunits made in the cytoplasm. There is evidence that the catalytic centers (heme a and copper) are associated with the mitochondrially-made subunits, but the role of the cytoplasmically-made subunits has remained open. Using a gene interruption technique, we have now constructed a Saccharomyces cerevisiae mutant which lacks the largest of the cytoplasmically-made subunits (subunit IV). This mutant is devoid of cyanide-sensitive respiration, the absorption spectrum of cytochrome aa3 and cytochrome c oxidase activity. It still contains the other cytochrome c oxidase subunits but these are not assembled into a stable complex. Active cytochrome c oxidase was restored to the mutant by introducing a plasmid-borne wild-type subunit IV gene; no restoration was seen with a gene carrying an internal deletion corresponding to amino acid residues 28-66 of the mature subunit. Subunit IV is thus necessary for proper assembly of cytochrome c oxidase.